Taqwīm Barnāmij Ta'limi al-Mufradāt bi Ma'had Fadhlul Fadhlan Al-Islamiy Semarang Min Khilali at-Tikror: The Evaluation of the Vocabulary-Learning-Program (VLP) at the Fadhlul-Fadhlan Islamic Institute Based-on the Repetition Method - Siti Luthfin Nuuriyyah; Inayah, Inayah; Muhammad Ahsanul Husna; Asma’ Na’im Jamil Abu Samra (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
The high urgency of mastering Arabic, especially mufrodat, in Fadhlul Fadhlan Islamic Boarding School encourages systematic efforts in the learning process. The Tikror method, with an emphasis on intensive repetition, is believed to be a key strategy to strengthen the memorization and application of mufrodat in the daily interactions of the students. This study aims to evaluate the vocabulary learning program through the tikror method at Pondok Pesantren Fadhlul Fadhlan Semarang. Vocabulary learning is a key component in Arabic language instruction, designed to enrich students' vocabulary and improve their understanding of the language. The tikror method, which focuses on word repetition, is expected to help students effectively memorize and comprehend vocabulary. This research employs a qualitative approach, with the subjects being teachers and students at Pondok Pesantren Fadhlul Fadhlan Semarang. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted using Miles and Huberman's model with data collection, data reduction, and conclusions. The findings show that the application of the tikror method is effective in improving students' ability to memorize and understand vocabulary. Repeating words during lessons helps students better retain the vocabulary taught. However, some challenges were found, such as a lack of variation in repetition techniques and limited time for optimal repetition. Despite these challenges, the tikror method has a positive effect on students' motivation to learn Arabic. Therefore, it is recommended that the tikror method be improved and combined with other teaching methods to enhance the effectiveness of vocabulary learning at this pesantren. Keywords: Arabic Learning, Evaluation of Program, Fadhlul Fadhlan Islamic Institute, Repetition Method, Tikror Method, Vocabulary Learning.